Principals’ and Science Teachers’ awareness of the concepts of Sustainable Development and Education for Sustainable Development - Nithlavarnan, A. (Academic Society for Research Excellence, 2018)
Sustainability issues have increased significantly in Sri Lanka like as globe. To provide a proper education to the educational community and general public is one of the more effective strategies to solve these problems. Education for Sustainable Development (ESD)-enriched Education forms the foundation for these initiatives. Compared with other countries, Sri Lanka is far behind in focusing on the ESD initiatives and is challenged with the task of embedding ESD at national, school wide and subject levels. This study attempts to identify the Principals’ and Science Teachers’ awareness of the concepts of Sustainable Development (SD) and ESD at secondary schools in Northern Province of Sri Lanka. The evaluation of awareness of the concepts of SD and ESD among change agents is important for effective implementation of ESD through general education in Sri Lanka. Qualitative method was used for data collection and data analysis. Interviews were conducted with 13 principals and 24 Science teachers from 13 secondary schools in Northern Province of Sri Lanka. The study revealed that the interviewees do not have a clear understanding of the concept of Sustainable Development (SD). Substantial numbers of the interviewees acknowledged the centrality of Environmental (17.64%), Economic (11.76%) and Social (11.76%) factors but only 17.64% have highlighted all three factors. Moreover, 41.17% interviewees have not stated any of the three aspects. Further this study revealed that a majority of change agents have a poor understanding about the concept of Education for Sustainable Development (ESD). Notable findings were that only 15.38 % have highlighted a comprehensive definition of ESD. However, 76.92% participants have mentioned views partially related to ESD but 7.69% participants have not mentioned any of the dimensions of SD. However, most of them have gained training on ESD in related sub-topics. Sri Lankan educational agencies should initiate appropriate professional development programmes for the above change agents including ESD aspects in content and pedagogy, further to restructuring the pre-service and in-service teacher education programme with respect to ESD.
Keywords: Awareness; Sustainable Development (SD); Education for Sustainable Development (ESD)